Blanche of Castile: Queen of France - Grant, Lindy (Yale University Press, 2016)
Princess of Castile -- The Lord Louis and the Lady Blanche -- King Louis VIII and Queen Blanche -- Queen regent -- Queen dowager -- The crusade regency -- Family, friends and familia -- Religion, the church and other faiths -- Piety and devotion -- The culture of the court -- Legitimacy and authority -- Ruler and counsellor -- The image of the queen